Evaluation of universal immunohistochemical screening of sebaceous neoplasms in a service setting. (14th January 2018) - Schon, K.; Rytina, E.; Drummond, J.; Simmonds, J.; Abbs, S.; Sandford, R.; Tischkowitz, M.
Summary: Background: Muir–Torre syndrome (MTS) is a subtype of Lynch syndrome, which encompasses the combination of sebaceous skin tumours or keratoacanthomas and internal malignancy, due to mutations in DNA mismatch repair genes. Sebaceous neoplasms (SNs) may occur before other malignancies, and may lead to the diagnosis, which allows testing of other family members, cancer surveillance, risk‐reducing surgery or prevention therapies. Aim: To evaluate the efficacy of universal immunohistochemistry (IHC) screening of SNs in a service setting. Methods: Patients with SNs were ascertained by a regional clinical pathology service over a 3‐year period. Results of tumour IHC, clinical genetics notes and germline genetic testing were retrospectively reviewed. Results: In total, 62 patients presented with 71 SNs; 9 (15%) of these patients had previously diagnosed MTS. Tumour IHC was performed for 50 of the 53 remaining patients (94%); 26 (52%) had loss of staining of one or more mismatch repair proteins. Fifteen patients were referred to the Clinical Genetics department, and 10 patients underwent germline genetic testing. Two had a new diagnosis of MTS confirmed, with heterozygous pathogenic mutations detected in the MSH2 and PMS2 genes (diagnostic yield 20%). The PMS2 mutation was identified in a 57‐year‐old woman with a sebaceous adenoma and history of endometrial cancer; to our knowledge, this is the first time a PMS2 mutation has been reported in MTS. Conclusions: Universal IHC screening of SNs is an effective method to identify cases for further genetic evaluation. Rates of referral to clinical genetics were only moderate (58%). Increased awareness of MTS could help improve the rate of onward referral.